Penerapan PENERAPAN NEAR FIELD COMMUNICATION PADA SISTEM PEMBAYARAN OTOMATIS TRANSPORTASI BUS BERBASIS INTERNET OF THINGS - Yuri Nur Kholipa; Dahlia Widyaestoeti; Andik Eko Kristus Pramuko (Universitas Widyatama, 2021)
The payment system goes from a manual to a cash transaction to a digital payment system. Automatic payment systems with NFC technology designed on this research. Analysis of business processes and systems analysis. Unified modelling language is designed using the waterfall method, database design, and user interface. The result of this study is a web that can read passenger data from applying NFC, cut off the passenger balance and the automatically transfer of notification on a telegram application with the help of a iot that serves as a connectivity. The assessment of the black box testing on the system with the user module value degree is 0.91.